Genetic diversity assessment of walnut (Juglans regia L.) genotypes from inner Anatolia region Türkiye using ISSR and RAPD markers - Yeter Çilesiz (Scientific Reports)
Abstract Common walnut (Juglans regia L.) is a globally important nut crop valued for its nutritional and economic benefits. Despite Türkiye’s importance as a walnut producer, molecular characterization of local genotypes, particularly from historically cultivated regions such as inner Anatolia remains limited. This study assessed the genetic diversity of 18 walnut genotypes from the inner Anatolia region, Türkiye using two molecular marker systems, including Inter-Simple Sequence Repeat (ISSR) and Random Amplified Polymorphic DNA (RAPD). The polymorphic bands were scored to calculate Jaccard similarity coefficients. Genetic relationships were analyzed using UPGMA dendrograms and Principal Component Analysis (PCA). A total of 72 bands (54 polymorphic; 75.0%) were generated by nine ISSR primers, and 53 bands (42 polymorphic; 79.2%) by five RAPD primers. Both marker systems indicated moderate genetic diversity within the genotypes. Genotypes ‘G3’, ‘G6’, and ‘G9’ had identical banding patterns (similarity = 1.00), likely attributable to their proximate geographic origin and same propagation history, whereas ‘G12’ and ‘G14’ were identified as genetically different. Population structure analysis demonstrated consistent clustering patterns, revealing both homogeneous and admixed genotypes. The Mantel test demonstrated a strong correlation (r = 0.81, p < 0.05) between genetic matrices derived from ISSR and RAPD, verifying marker congruence. The results highlight the effectiveness of using ISSR and RAPD markers as an economical method for evaluating genetic structure in under-characterized germplasm. The identification of genetically different genotypes is crucial for conservation and breeding techniques aimed at enhancing traits and genetic resilience in walnuts.